Stylistic virtue and Victorian fiction : form, ethics, and the novel - Sussman, Matthew (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
What is style, and why does it matter? This book answers these questions by recovering the concept of'stylistic virtue,' once foundational to rhetoric and aesthetics but largely forgotten today. Stylistic virtues like'ease' and'grace' are distinguishing properties that help realize a text's essential character. First described by Aristotle, they were integral to the development of formalist methods and modern literary criticism. The first half of the book excavates the theory of stylistic virtue during its period of greatest ascendance, in the late eighteenth and nineteenth centuries, when belletristic rhetoric shaped how the art of literary style and'the aesthetic' were understood. The second half offers new readings of Thackeray, Trollope, and Meredith to show how stylistic virtue changes our understanding of style in the novel and challenges conventional approaches to interpreting the ethics of art.
Introduction: What is the stylistic virtue? -- Stylistic virtue and the rise of literary formalism -- Stylistic virtue between moralism and aestheticism -- Virtue theory and the nature of the aesthetic -- Thackeray's grace -- Trollope's ease and lucidity -- Meredith's fervidness -- Afterword: Stylistic virtue and literary value.
Title from publisher's bibliographic system (viewed on 11 Jun 2021).
Keywords: English fiction -- 19th century -- History and criticism; English language -- Rhetoric; English language -- Style; England -- Intellectual life -- 19th century